PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE VIVO DI KOTA DEPOK - Eigis Yani Pramularso; Nanang Lidwan; Mohammad Amas Lahat (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
Facing increasingly sharp competition, companies continue to make efforts to make their products the choice in consumer purchasing decisions. Companies can optimize their brand image and improve the quality of the products they produce so that they continue to exist when faced with other company products. This research aims to determine the influence of brand image and product quality on purchasing decisions for the Vivo Smartphone. Data collection in this research used a questionnaire and a total of 45 respondents were obtained. The research results illustrate that there is a positive and significant influence between brand image on purchasing decisions, there is a positive and significant influence between product quality on purchasing decisions, and there is a positive and significant influence between brand image and product quality on purchasing decisions for Vivo smartphones.